Communication Skills for Business Professionals - Lawson, Celeste, Dr.; Gill, Robert, Dr.; Feekery, Angela; Witsel, Mieke; Lewis, Michael A. (Professor of management); Cenere, Philip (Cambridge : Cambridge University Press, 2019)
Communication Skills for Business Professionals, second edition, is a student-friendly introduction to effective communication in the workplace. Engagingly written, the text covers foundational topics such as audience, influence, channels, conflict and persuasion, before investigating more complex areas such as intercultural communication, virtual communication, researching in the era of 'fake news' and strategies for successful written communication. Taking a broad and current approach to concepts of communication and workplaces, Communication Skills for Business Professionals explores situations from virtual meetings between indie creatives, to speeches given by politicians, while still covering more traditional forms of professional communication, such as pitching to boards and memos. New pedagogical features such as interactive questions and answers, skill builder class activities, margin definitions and links to online content make this book indispensable for teachers and students of communications alike.
Title from publisher's bibliographic system (viewed on 08 Apr 2020).
Keywords: elektronické knihy; electronic books; Communication in management; Business communication; Business communication -- Study and teaching